"My muse will have a story to paint" : selected prose of Ludovico Ariosto - Ariosto, Lodovico, 1474-1533 (Lorenzo da Ponte Italian library series., 2010)
Looney's elegant, careful translation provides us with the first extensive selection of Ariosto's prose works in English, and enriches our understanding of one of Italy's most important Renaissance writers."--Pub. desc.